2022
DOI: 10.1111/ecc.13587
|View full text |Cite
|
Sign up to set email alerts
|

The quality of life of regional and remote cancer caregivers in Australia

Abstract: Objective: This study compares the well-being of rural caregivers with that of the general population and explores the potential drivers of poorer outcomes.Method: Patient-caregiver dyads (n = 241) residing in regional or remote Queensland, Australia, reported on QoL, chronic illness, caregiver burden, depression, anxiety and stress. Caregiver outcomes were compared with population norms and patient outcomes. Multiple regressions were conducted to identify factors associated with poorer caregiver outcomes.Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…Overall, this study indicates there is a need to ensure adequate support is available and accessible to rural cancer caregivers. This need is supported by previous research reporting poorer mental wellbeing among rural cancer caregivers, 16 as well as high unmet needs for supportive care 17 and challenges in accessing local support services 19,36 . Thus, system‐wide changes are needed to address these challenges.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…Overall, this study indicates there is a need to ensure adequate support is available and accessible to rural cancer caregivers. This need is supported by previous research reporting poorer mental wellbeing among rural cancer caregivers, 16 as well as high unmet needs for supportive care 17 and challenges in accessing local support services 19,36 . Thus, system‐wide changes are needed to address these challenges.…”
Section: Discussionmentioning
confidence: 82%
“…Currently, cancer caregivers living in regional and remote (i.e. rural) Australia report poorer than average mental wellbeing compared to population norms 16 . They also report high unmet needs for practical support (e.g.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Although progress has been made in understanding the occurrence of mental comorbidity and psychosocial distress in cancer patients, comparatively little is known about the course of psychological comorbidity and psychosocial distress in the early survivorship phase in patients and their relatives. Relatives and informal caregivers experience high levels of emotional distress such as anxiety, helplessness and hopelessness, depressed mood, and impaired quality of life ( Sklenarova et al, 2015 ; Thana et al, 2021 ; Goodwin et al, 2022 ). Acute, long-term and late physical and psychosocial impairments due to the partner’s cancer, role changes, difficulties in coping with the disease or impaired family interaction processes are stressors for the relatives ( Hagedoorn et al, 2008 ).…”
Section: Introductionmentioning
confidence: 99%
“…Prior studies with other cancer carers have reported positive changes 33 and benefits 34 . At the same time, there is literature documenting impaired QOL for carers of people with MM, 6 and poorer mental health‐related QOL for rural cancer carers in Australia relative to population norms 35 . It is important to consider and assess both burden and benefits, and researchers or health professionals should not always assume that carers for people with high needs will always experience this as a burden.…”
Section: Discussionmentioning
confidence: 99%